The impact of regional original income and balance funds on local government financial performance: an Islamic perspective in Central Java, Indonesia - Maghfiroh, Tsaniyatul; Warno, Warno; Muheramtohadi, Singgih (Journal of Islamic Economics Management and Business (JIEMB), 2024)
This study examines the effects of regional original income (PAD) and balance funds on the financial performance of local governments in Central Java Province from 2019 to 2023. The research explores the mediating role of capital expenditure in these relationships, incorporating both conventional economic and Islamic financial perspectives. Utilizing quantitative analysis and path analysis, the study draws on secondary data from 35 local governments. The findings reveal that PAD positively affects financial performance, enhancing fiscal independence, while balance funds negatively impact both financial performance and capital expenditure due to fiscal dependency. Capital expenditure was found not to mediate the relationships between PAD, balance funds, and financial performance. These results highlight the need for local governments to reduce dependency on balance funds and focus on sustainable revenue generation through PAD, in line with Islamic ethical principles of stewardship, justice, and public welfare. The study contributes to understanding fiscal independence within an Islamic framework, with recommendations for future research to further explore these dynamics.